Loss channels in triplet–triplet annihilation photon upconversion: importance of annihilator singlet and triplet surface shapes. Issue 17 (12th April 2017) - Gray, Victor; Dreos, Ambra; Erhart, Paul; Albinsson, Bo; Moth-Poulsen, Kasper; Abrahamsson, Maria
Abstract : Differences in triplet–triplet annihilation photon upconversion efficiencies between structurally similar annihilators can be understood in terms of singlet and triplet surface shapes. Abstract : Triplet–triplet annihilation photon upconversion (TTA-UC) can, through a number of energy transfer processes, efficiently combine two low frequency photons into one photon of higher frequency. TTA-UC systems consist of one absorbing species (the sensitizer) and one emitting species (the annihilator). Herein, we show that the structurally similar annihilators, 9, 10-diphenylanthracene (DPA, 1 ), 9-(4-phenylethynyl)-10-phenylanthracene (2 ) and 9, 10-bis(phenylethynyl)anthracene (BPEA, 3 ) have very different upconversion efficiencies, 15.2 ± 2.8%, 15.9 ± 1.3% and 1.6 ± 0.8%, respectively (of a maximum of 50%). We show that these results can be understood in terms of a loss channel, previously unaccounted for, originating from the difference between the BPEA singlet and triplet surface shapes. The difference between the two surfaces results in a fraction of the triplet state population having geometries not energetically capable of forming the first singlet excited state. This is supported by TD-DFT calculations of the annihilator excited state surfaces as a function of phenyl group rotation. We thereby highlight that the commonly used "spin-statistical factor" should be used with caution when explaining TTA-efficiencies. Furthermore, we show that the precious metal free zinc octaethylporphyrin (ZnOEP) can be used for efficient sensitization and that the upconversion quantum yield is maximized when sensitizer–annihilator spectral overlap is minimized (ZnOEP with2 ).